Exploration of the Potential Mechanism of Tao Hong Si Wu Decoction for the Treatment of Breast Cancer Based on Network Pharmacology and In Vitro Experimental Verification - Huang, Shi; Chen, Yan; Pan, Lingyu; Fei, Changyi; Wang, Ni; Chu, Furui; Peng, Daiyin; Duan, Xianchun; Wang, Yongzhong (Frontiers in Oncology, 2021)
Background: Tao Hong Si Wu Decoction (THSWD) is a well-known traditional Chinese medicine used clinically alone or combined with drugs to treat breast cancer. However, there has been no study to date on the underlying mechanisms of its therapeutic effects. Objectives: This study applied the network pharmacology approach to explore the mechanisms of THSWD in the treatment of breast cancer. Methods: The active ingredients of THSWD were screened according to Lipinski’s rule of five based on the 107 ingredients of THSWD identified by UPLC-Q-TOF-MSE. The targets of THSWD and breast cancer from multiple databases were collected, and a Compound-Target-Pathway network based on protein-protein interaction (PPI) was constructed. Gene ontology (GO) analysis and KEGG pathway analysis were performed via the DAVID server. Molecular docking studies verified the selected key ingredients and key targets. The results of network pharmacology were verified by in vitro experiments. Including the effects of THSWD drug-containing rat serum (THSWD serum) on cell proliferation, and on the targets HRAS, MAPK1, AKT1, GRB2, and MAPK14 were assayed by RT-qPCR and Western blot assays. Results: In total, 27 active ingredients including 8 core components, were obtained from 107 ingredients and 218 THSWD target genes for the treatment of breast cancer were identified. THSWD is active in the treatment of breast cancer by targeting Ras, FoxO, PI3K-Akt and other signaling pathways. MCF-7 and MDA-MB-231 cell proliferation was inhibited by THSWD serum in a time and concentration dependent manner. THSWD could regulated the RNA and protein expression of core targets HRAS, MAPK1, AKT1, GRB2, and MAPK14 for treatment of breast cancer. Conclusion: The results of network pharmacology study showed that THSWD is active against breast cancer by intervening with multiple targets and pathways. Luteolin, kaempferol, senkyunolide E, and other 8 compounds may be the core active ingredients of THSWD in the treatment of breast cancer. THSWD treatment of breast cancer may be related to targeting Ras, FoxO, PI3K-Akt, and other signal pathways associated with the core targets HRAS, MAPK1, AKT1, GRB2, and MAPK14.